Let \[P\] be a point on the parabola \[{{y}^{2}}-2y-4x+5=0\], such that the tangent on the parabola at \[P\] intersects the directrix at a point \[Q\]. Let \[R\] be the point that divides the line segment \[QP\] externally in the ratio \[\dfrac{1}{2}:1\]. Find the locus of \[R\].
Answer
Verified
511.8k+ views
Hint: Write the equation of tangent, get points \[Q\] and \[P\] and then use \[x=\dfrac{m{{x}_{2}}-n{{x}_{1}}}{m-n}\] and \[y=\dfrac{m{{y}_{2}}-n{{y}_{1}}}{m-n}\].
We are given a point \[P\] on the parabola \[{{y}^{2}}-2y-4x+5=0\] such that tangent on the parabola at \[P\] intersect the directrix at \[Q\].
We have to find the locus of \[R\] which divides \[QP\] externally in the ratio \[\dfrac{1}{2}:1\].
First of all, we will convert the parabola into its standard form
We take, \[{{y}^{2}}-2y-4x+5=0\]
Or, \[{{y}^{2}}-2y=4x-5\]
Adding \[1\] on both sides,
We get, \[{{y}^{2}}-2y+1=4x-5+1\]
Since we know that \[{{a}^{2}}+{{b}^{2}}-2ab={{\left( a-b \right)}^{2}}\]
Therefore, we get \[{{\left( y-1 \right)}^{2}}=4x-4\]
Or, \[{{\left( y-1 \right)}^{2}}=4\left( x-1 \right)\]
Let \[y-1=Y\] and \[x-1=X\]
So, we get parabola \[{{Y}^{2}}=4X\] which is the standard form of a parabola.
Now, we know that any general point on the parabola is \[\left( a{{t}^{2}},2at \right)\].
By comparing parabola \[{{Y}^{2}}=4X\] with general parabola \[{{y}^{2}}=4ax\],
We get \[4a=4\]
Therefore, we get \[a=1\]
Now, we know that any general point on the parabola \[{{y}^{2}}=4ax\] is \[\left( a{{t}^{2}},2at \right)\]
Since, \[a=1\]
We get, \[P\left( X,Y \right)=P\left( {{t}^{2}},2t \right)\]
We know that tangent at point \[\left( a{{t}^{2}},2at \right)\] is given by \[ty=x+a{{t}^{2}}\]
Since \[a=1\], we get equation of tangent at \[P\left( {{t}^{2}},2t \right)\] as \[tY=X+{{t}^{2}}....\left( i \right)\]
We know that equation of directrix is
\[X=-a\]
Therefore, we get \[X=-1\]
Or, \[X+1=0\]
Since we know that \[Q\] is a point of intersection of tangents and directrix is \[X=-1\].
Therefore, we will put \[X=-1\] in the equation \[\left( i \right)\] to find the \[Y\] coordinate.
So, \[tY=X+{{t}^{2}}\]
\[\Rightarrow tY=-1+{{t}^{2}}\]
\[Y=\dfrac{{{t}^{2}}-1}{t}\]
Therefore, we get a point \[Q\left( X,Y \right)=\left( -1,\dfrac{{{t}^{2}}-1}{t} \right)\]
Let the point \[R\] be \[\left( h,k \right)\] which divides \[QP\] externally in the ratio \[\dfrac{1}{2}:1\]
We know that if \[R\left( x,y \right)\] divides \[Q\left( {{x}_{1}},{{y}_{1}} \right)\] and \[P\left( {{x}_{2}},{{y}_{2}} \right)\]in the ratio \[m:n\]
Then, \[x=\dfrac{m\left( {{x}_{2}} \right)-n\left( {{x}_{1}} \right)}{\left( m-n \right)}\]
\[y=\dfrac{m\left( {{y}_{2}} \right)-n\left( {{y}_{1}} \right)}{\left( m-n \right)}\]
Here, we have \[R\left( x,y \right)=\left( h,k \right)\]
\[Q\left( {{x}_{1}},{{y}_{1}} \right)=\left( -1,\dfrac{{{t}^{2}}-1}{t} \right)\]
\[P\left( {{x}_{2}},{{y}_{2}} \right)=\left( {{t}^{2}},2t \right)\]
\[m=\dfrac{1}{2},n=1\]
So, we get \[h=\dfrac{\dfrac{1}{2}\left( {{t}^{2}} \right)-1\left( -1 \right)}{\dfrac{1}{2}-1}\]
\[h=\dfrac{\dfrac{{{t}^{2}}}{2}+1}{\dfrac{-1}{2}}\]
\[h=-\left( {{t}^{2}}+2 \right)\]
Or \[{{t}^{2}}=-2-h....\left( ii \right)\]
And \[k=\dfrac{\dfrac{1}{2}\left( 2t \right)-1\left( \dfrac{{{t}^{2}}-1}{t} \right)}{\dfrac{1}{2}-1}\]
\[k=\dfrac{t-\left( \dfrac{{{t}^{2}}}{t}-\dfrac{1}{t} \right)}{\dfrac{-1}{2}}\]
\[k=-2\left[ t-\left( t-\dfrac{1}{t} \right) \right]\]
\[k=\dfrac{-2}{t}\]
By squaring both the sides,
We get, \[{{k}^{2}}=\dfrac{4}{{{t}^{2}}}\]
Now, by putting the value of \[{{t}^{2}}\] from equation \[\left( ii \right)\]
We get \[{{k}^{2}}=\dfrac{4}{\left( -2-h \right)}\]
By cross multiplying, we get
\[\Rightarrow -{{k}^{2}}\left( h+2 \right)=4\]
To get the locus, we will replace \[h\]by \[X\] and \[k\]by \[Y\].
We get, \[-{{Y}^{2}}\left( X+2 \right)=4\]
As we had assumed that \[X=x-1\] and \[Y=y-1\]
We get, \[-{{\left( y-1 \right)}^{2}}\left( x-1+2 \right)=4\]
\[-{{\left( y-1 \right)}^{2}}\left( x+1 \right)=4\]
Or, \[{{\left( y-1 \right)}^{2}}\left( x+1 \right)+4=0\]
Note: Always convert the given parabola into standard parabola \[{{y}^{2}}=4ax\] and then use the general equation of tangents, normals etc. Also, students often forget to convert \[X\] to \[x\] and \[Y\] to \[y\] and get wrong answers. So this step must be kept in mind.
We are given a point \[P\] on the parabola \[{{y}^{2}}-2y-4x+5=0\] such that tangent on the parabola at \[P\] intersect the directrix at \[Q\].
We have to find the locus of \[R\] which divides \[QP\] externally in the ratio \[\dfrac{1}{2}:1\].
First of all, we will convert the parabola into its standard form
We take, \[{{y}^{2}}-2y-4x+5=0\]
Or, \[{{y}^{2}}-2y=4x-5\]
Adding \[1\] on both sides,
We get, \[{{y}^{2}}-2y+1=4x-5+1\]
Since we know that \[{{a}^{2}}+{{b}^{2}}-2ab={{\left( a-b \right)}^{2}}\]
Therefore, we get \[{{\left( y-1 \right)}^{2}}=4x-4\]
Or, \[{{\left( y-1 \right)}^{2}}=4\left( x-1 \right)\]
Let \[y-1=Y\] and \[x-1=X\]
So, we get parabola \[{{Y}^{2}}=4X\] which is the standard form of a parabola.
Now, we know that any general point on the parabola is \[\left( a{{t}^{2}},2at \right)\].
By comparing parabola \[{{Y}^{2}}=4X\] with general parabola \[{{y}^{2}}=4ax\],
We get \[4a=4\]
Therefore, we get \[a=1\]
Now, we know that any general point on the parabola \[{{y}^{2}}=4ax\] is \[\left( a{{t}^{2}},2at \right)\]
Since, \[a=1\]
We get, \[P\left( X,Y \right)=P\left( {{t}^{2}},2t \right)\]
We know that tangent at point \[\left( a{{t}^{2}},2at \right)\] is given by \[ty=x+a{{t}^{2}}\]
Since \[a=1\], we get equation of tangent at \[P\left( {{t}^{2}},2t \right)\] as \[tY=X+{{t}^{2}}....\left( i \right)\]
We know that equation of directrix is
\[X=-a\]
Therefore, we get \[X=-1\]
Or, \[X+1=0\]
Since we know that \[Q\] is a point of intersection of tangents and directrix is \[X=-1\].
Therefore, we will put \[X=-1\] in the equation \[\left( i \right)\] to find the \[Y\] coordinate.
So, \[tY=X+{{t}^{2}}\]
\[\Rightarrow tY=-1+{{t}^{2}}\]
\[Y=\dfrac{{{t}^{2}}-1}{t}\]
Therefore, we get a point \[Q\left( X,Y \right)=\left( -1,\dfrac{{{t}^{2}}-1}{t} \right)\]
Let the point \[R\] be \[\left( h,k \right)\] which divides \[QP\] externally in the ratio \[\dfrac{1}{2}:1\]
We know that if \[R\left( x,y \right)\] divides \[Q\left( {{x}_{1}},{{y}_{1}} \right)\] and \[P\left( {{x}_{2}},{{y}_{2}} \right)\]in the ratio \[m:n\]
Then, \[x=\dfrac{m\left( {{x}_{2}} \right)-n\left( {{x}_{1}} \right)}{\left( m-n \right)}\]
\[y=\dfrac{m\left( {{y}_{2}} \right)-n\left( {{y}_{1}} \right)}{\left( m-n \right)}\]
Here, we have \[R\left( x,y \right)=\left( h,k \right)\]
\[Q\left( {{x}_{1}},{{y}_{1}} \right)=\left( -1,\dfrac{{{t}^{2}}-1}{t} \right)\]
\[P\left( {{x}_{2}},{{y}_{2}} \right)=\left( {{t}^{2}},2t \right)\]
\[m=\dfrac{1}{2},n=1\]
So, we get \[h=\dfrac{\dfrac{1}{2}\left( {{t}^{2}} \right)-1\left( -1 \right)}{\dfrac{1}{2}-1}\]
\[h=\dfrac{\dfrac{{{t}^{2}}}{2}+1}{\dfrac{-1}{2}}\]
\[h=-\left( {{t}^{2}}+2 \right)\]
Or \[{{t}^{2}}=-2-h....\left( ii \right)\]
And \[k=\dfrac{\dfrac{1}{2}\left( 2t \right)-1\left( \dfrac{{{t}^{2}}-1}{t} \right)}{\dfrac{1}{2}-1}\]
\[k=\dfrac{t-\left( \dfrac{{{t}^{2}}}{t}-\dfrac{1}{t} \right)}{\dfrac{-1}{2}}\]
\[k=-2\left[ t-\left( t-\dfrac{1}{t} \right) \right]\]
\[k=\dfrac{-2}{t}\]
By squaring both the sides,
We get, \[{{k}^{2}}=\dfrac{4}{{{t}^{2}}}\]
Now, by putting the value of \[{{t}^{2}}\] from equation \[\left( ii \right)\]
We get \[{{k}^{2}}=\dfrac{4}{\left( -2-h \right)}\]
By cross multiplying, we get
\[\Rightarrow -{{k}^{2}}\left( h+2 \right)=4\]
To get the locus, we will replace \[h\]by \[X\] and \[k\]by \[Y\].
We get, \[-{{Y}^{2}}\left( X+2 \right)=4\]
As we had assumed that \[X=x-1\] and \[Y=y-1\]
We get, \[-{{\left( y-1 \right)}^{2}}\left( x-1+2 \right)=4\]
\[-{{\left( y-1 \right)}^{2}}\left( x+1 \right)=4\]
Or, \[{{\left( y-1 \right)}^{2}}\left( x+1 \right)+4=0\]
Note: Always convert the given parabola into standard parabola \[{{y}^{2}}=4ax\] and then use the general equation of tangents, normals etc. Also, students often forget to convert \[X\] to \[x\] and \[Y\] to \[y\] and get wrong answers. So this step must be kept in mind.
Recently Updated Pages
Master Class 11 Accountancy: Engaging Questions & Answers for Success
Glucose when reduced with HI and red Phosphorus gives class 11 chemistry CBSE
The highest possible oxidation states of Uranium and class 11 chemistry CBSE
Find the value of x if the mode of the following data class 11 maths CBSE
Which of the following can be used in the Friedel Crafts class 11 chemistry CBSE
A sphere of mass 40 kg is attracted by a second sphere class 11 physics CBSE
Trending doubts
10 examples of friction in our daily life
Difference Between Prokaryotic Cells and Eukaryotic Cells
One Metric ton is equal to kg A 10000 B 1000 C 100 class 11 physics CBSE
State and prove Bernoullis theorem class 11 physics CBSE
What organs are located on the left side of your body class 11 biology CBSE
Define least count of vernier callipers How do you class 11 physics CBSE